DIGITAL FUNDRAISING BASED ZAKAT COLLECTION STRATEGY IN MEDAN CITY LAZISMU - Arifin Lubis, Muhammad (Proceeding International Seminar of Islamic Studies, 2023)
There is still a significant gap between the potential and actuality of zakat collection, the lack of zakat literacy among Muslims, and the preference for direct distribution as factors causing the difficulty in managing zakat in Indonesia. The purpose of this study is to maximize zakat collection funds and see an increase in zakat fund collection after utilizing online media at Lazismu Medan City. The research method used in this study is a qualitative method with a literature review approach, in which researchers collect information from international and national publications. Information collected from these journals was then used as research material for this study. The results of the study found that the results of this study found that to maximize zakat collection funds at Lazismu, Medan City made the latest innovation, namely digital fundraising. Utilization of online social media platforms, namely as a forum to invite or urge the public to give zakat and also zakat pick-up services and transfer of banking services is very helpful for the community and also for Lazismu to experience an increase in zakat collection. Zakat campaign tactics must be developed, including but not limited to: education, service promotion, program promotion and achievements, generating empathy through advertising, and building collaboration with stakeholders. Utilization of online social media platforms, namely as a forum to invite or urge the public to give zakat and also zakat pick-up services and transfer of banking services is very helpful for the community and also for Lazismu to experience an increase in zakat collection. Zakat campaign tactics must be developed, including but not limited to: education, service promotion, program promotion and achievements, generating empathy through advertising, and building collaboration with stakeholders. Utilization of online social media platforms, namely as a forum to invite or urge the public to give zakat and also zakat pick-up services and banking service transfers really help the community and also Lazismu so that they experience an increase in zakat collection. Zakat campaign tactics must be developed, including but not limited to: education, promotion of services, promotion of programs and achievements, generating empathy through advertising, and building collaboration with stakeholders.